Designing a Marketing Strategy for Bawis Habati Fish Chips Using the Quantitative Strategic Planning Matrix (QSPM) Method - Ridwan, Mochamad; Tosungku, La Ode Ahmad Safar; Pawitra, Theresia Amelia (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
Habati fish chips is one of the Micro, Small, and Medium Enterprises (MSME) in the food industry in the city of Bontang. Habati MSME still applies simple promotion methods and does not target the teenage market to compete. This research aims to design a marketing strategy for Habati fish chips in Bontang city, targeting a new market segment, which is teenagers. The marketing strategy analysis is conducted in three stages: input stage, matching stage, and decision stage. In the input stage, Internal Factor Evaluation (IFE) matrix is used with a score of 2.338, External Factor Evaluation (EFE) matrix with a score of 2.764, and Competitive Profile Matrix (CPM) to determine the position of Habati MSME compared to Pak Ucil and Abadi Rasa based on the perspective of potential consumers. The matching stage is then used to formulate marketing strategies using the Internal-External (IE) matrix and Strengths, Weaknesses, Opportunities, and Threats (SWOT) matrix. Based on the overall methods used, the final stage is the decision stage. The decision stage utilizes the Quantitative Strategic Planning Matrix (QSPM) to select prioritized alternative strategies that can be implemented by Habati MSME. The research results provide seven alternative strategies with one prioritized strategy having the highest Total Attractive Score (TAS), which is to increase product sales through online marketing, utilizing marketplaces, and promoting product advantages, with a TAS of 7.074.